Kepentingan dalam Mutasi Aparatur Sipil Negara di Kabupaten Bungo pada tahun 2021 - Ananda, Garry; Syaiful; Tamrin (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2024)
The influence of politics on the bureaucracy or commonly known as the politicization of the bureaucracy is one of the phenomena that often occurs in government bodies. After the regional head elections, the desire to reorganize civil servants or the state civil apparatus within the scope of regional administration can increase. This thesis aims to identify and analyze the interests of regional heads in politicizing the bureaucracy in the implementation of ASN mutations after the regional head elections took place in the Bungo Regency government environment. This study uses a qualitative method with a case study approach to answer research question. The theory used is the theory of bureaucratic politicization by Barbara Geddes. The results of this study indicate that the Bungo Regent's interest in the bureaucracy is to want a loyal bureaucratic machine so that it is then able to fulfill its interests in realizing the vision and mission in terms of developing Bungo Regency and also other interests such as maintaining its power.